Nutritional strategies in the treatment of diabetes mellitus: bibliographic review (Research, Society and Development, 2020)
The present study aims to show the effects of a diet therapy intervention on type 1 and 2 diabetes mellitus, through a literature review. As a qualitative review this work used as bibliographic sources scientific articles were explored in the databases (PubMed), (SciELO), (LILACS) and (ScienceDirect) using the Descriptors in Health Sciences (DeCS): “Diabetes Mellitus”. , “Diet Therapy”, “Nutritional Needs” or their English equivalents. In total, 14 articles met the methodological criteria and had their results tabulated for better analysis and understanding. Most of the articles showed that the improvement in diabetes patients is associated with a healthy diet in which macronutrients are evenly divided. It was concluded that patients with diabetes mellitus have a variety of dietary options that have good sources of carbohydrates, lipids and proteins, thus being able to adapt them to their personal tastes for a better adherence to the diet.